2015
DOI: 10.1016/j.neuroimage.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of trial-driven and task Set-related control in primary visual cortex

Abstract: Task sets are task-specific configurations of cognitive processes that facilitate task-appropriate reactions to stimuli. While it is established that the trial-by-trial deployment of visual attention to expected stimuli influences neural responses in primary visual cortex (V1) in a retinotopically specific manner, it is not clear whether the mechanisms that help maintain a task set over many trials also operate with similar retinotopic specificity. Here, we address this question by using BOLD fMRI to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Sustained signals from the cingulo-opercular network are related to the maintenance of task sets (Dosenbach et al 2008; Nelson et al, 2010), though their precise function remains unclear (Dubis et al 2014). Recent work by our lab has demonstrated that sustained task-driven responses occur in early visual areas including V1 (Elkhetali et al 2015), but do not show the spatial specificity of cue-driven and stimulus-driven responses (Griffis et al 2015b). While we have interpreted these sustained V1 responses as reflecting ongoing task maintenance signals that are likely to have originated in the cingulo-opercular network, it is unclear why this network would show preferential connectivity to the near-periphery of V1 during fixation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sustained signals from the cingulo-opercular network are related to the maintenance of task sets (Dosenbach et al 2008; Nelson et al, 2010), though their precise function remains unclear (Dubis et al 2014). Recent work by our lab has demonstrated that sustained task-driven responses occur in early visual areas including V1 (Elkhetali et al 2015), but do not show the spatial specificity of cue-driven and stimulus-driven responses (Griffis et al 2015b). While we have interpreted these sustained V1 responses as reflecting ongoing task maintenance signals that are likely to have originated in the cingulo-opercular network, it is unclear why this network would show preferential connectivity to the near-periphery of V1 during fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Task and stimulus details have been described in detail elsewhere (Elkhetali et al 2015; Griffis et al 2015b), and will only be briefly described here, as current analyses focus on the rest periods only. Task blocks consisted of unimodal and bimodal visual and auditory attention tasks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include differences in the cellular structure of retinal inputs to the lateral geniculate nucleus (LGN; Curcio and Allen, 1990; Dacey, 1993; Neitz et al, 2006), neuronal density (Collins et al, 2010), inter-regional connections (Hadjikhani and Tootell, 2000; Clavagnier et al, 2004; Palmer and Rosa, 2006), sensitivity to threatening stimuli (Bayle et al, 2009; Gomez et al, 2011), responses during cross-modal attention (Cate et al, 2009; Griffis et al, 2015), and modulation of activity by spatial attention (Roberts et al, 2007). Thus, it is reasonable to hypothesize that foveal vs. peripheral retinotopic representations in V1 might be differentially affected by processes such as aging.…”
Section: Introductionmentioning
confidence: 99%